PENGARUH EASE OF USE DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN GO-FOOD DI SEMARANG - Santoso, Liem, Alan Dharmasaputra; Juventius Wahyu Utama (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to determine the relationship between ease of use, price perception on purchasing decisions of the users on Go-Food delivery application in North Semarang district. Quantitative method using a purposive random sampling technique are used in this research. The sample size used in this research is 100 respondents. Data analysis used in this research uses validation tests, reliability tests, data normality tests and multiple regression tests. The results of this research show that there is a relationship between ease of use and price perception on purchasingmdecisions of the users on Go-Food delivery application in North Semarang district.